The crossed frontal aslant tract: A possible pathway involved in the recovery of supplementary motor area syndrome. Issue 3 (5th February 2018) - Baker, Cordell M.; Burks, Joshua D.; Briggs, Robert G.; Smitherman, Adam D.; Glenn, Chad A.; Conner, Andrew K.; Wu, Dee H.; Sughrue, Michael E.
Abstract: Introduction: Supplementary motor area (SMA) syndrome is a constellation of temporary symptoms that may occur following tumors of the frontal lobe. Affected patients develop akinesia and mutism but often recover within weeks to months. With our own case examples and with correlations to fiber tracking validated by gross anatomical dissection as ground truth, we describe a white matter pathway through which recovery may occur. Methods: Diffusion spectrum imaging from the Human Connectome Project was used for tractography analysis. SMA outflow tracts were mapped in both hemispheres using a predefined seeding region. Postmortem dissections of 10 cadaveric brains were performed using a modified Klingler technique to verify the tractography results. Results: Two cases were identified in our clinical records in which patients sustained permanent SMA syndrome after complete disconnection of the SMA and corpus callosum (CC). After investigating the postoperative anatomy of these resections, we identified a pattern of nonhomologous connections through the CC connecting the premotor area to the contralateral premotor and SMAs. The transcallosal fibers have projections from the previously described frontal aslant tract (FAT) and thus, we have termed this path the "crossed FAT." Conclusions: We hypothesize that this newly described tract may facilitate recovery from SMA syndrome by maintaining interhemispheric connectivity through the supplementary motor and premotor areas. Abstract : Through case examples and fiber tracking validated by gross anatomical dissection, we describe a white matter pathway through which supplementary motor area syndrome recovery may occur.